Peran Perancang Kurikulum dalam Pengembangan Pembelajaran Bahasa Asing untuk Pertahanan Negara di Kelas Hibrida - Kartika S. Hardjanti (Badan Pendidikan dan Pelatihan Kementerian Pertahanan, 2025)
Amidst the uncertainty and complexity of the world due to the Volatility, Uncertainty, Complexity, and Ambiguity (VUCA) era, curriculum development is one of the most important elements in the education system. The design of the right curriculum not only affects the quality of learning, but also the results achieved by students, especially in facing global challenges. Curriculum designers play an important role in adapting education to technological developments and changing industry needs. By using the right technology, they can create more efficient, inclusive, and relevant education and/or learning at various levels of education for future generations. This study uses a qualitative descriptive approach with a literature study to analyze the role of curriculum designers in developing foreign language learning for national defense in hybrid classes. The data collected were analyzed to empirically and theoretically describe the contribution of curriculum designers in creating a more effective learning environment. Theoretically, this study enriches the understanding of the role of curriculum designers, while practically, the results of the study can be a reference in developing foreign language curricula in educational institutions of ministries or institutions. The data obtained show that curriculum designers make a positive contribution to creating more effective learning, both offline and online, and play a role in creating a more efficient and adaptive educational environment. Innovation in curriculum design and teaching will create foreign language learning that is in accordance with the demands of the times.